Hubungan hematokrit dengan SGOT dan SGPT pada obesitas sentral - Reak, Aryant D.; Wantania, Frans E.; Waleleng, Bradley J. (e-CliniC, 2016)
Abstract: Obesity is a multifactorial disease secondary to excessive accumulation of fat tissue which can harm the health condition. Obesity occurs when a large and number of fat cells growing in a person's body. The adverse effect of obesity is not only related to total body weight, but also to the distribution of fat deposits. Central or visceral obesity has a higher risk for some diseases compared to diffuse accumulation of fat in the subcutaneous tissue. Central obesity can increase the hematocrit, as well as SGOT and SGPT values. This study was aimed to determine the correlation of hematocrit with SGOT and SGPT in central obesity. This was an analytical study with a cross sectional design. Samples were selected by using consecutive sampling method. Laboratory examinations were performed in Prokita laboratory from September 2016 to November 2016. The results of Spearman correlation analysis on the correlation between hematocrit and SGOT showed an r value of 0.162 and a p value of 0.419. Meanwhile, the correlation between hematocrit and SGPT showed an r value of 0.118 and a p value of 0.558. Conclusion: There was no correlation between hematocrit and either SGOT or SGPT in central obesity.Keywords: central obesity, hematocrit, SGOT, SGPTÂ Abstrak: Obesitas adalah suatu penyakit multifaktorial yang terjadi akibat akumulasi lemak jaringan berlebihan, sehingga dapat menggangu kesehatan. Efek merugikan obesitas tidak hanya berkaitan dengan berat badan total, tetapi juga distribusi simpanan lemak. Obesitas sentral atau visceral, memeliki risiko yang jauh lebih tinggi untuk beberapa penyakit dibandingkan dengan kelebihan akumulasi lemak difus dijaringan subkutis. Pada obesitas sentral dapat terjadi peningkatan nilai hematokrit, SGOT, dan SGPT. Penelitian ini bertujuan untuk mengetahui hubungan hematokrit dengan SGOT dan SGPT pada obesitas sentral. Jenis penelitian ialah analitik dengan desain potong lintang. Pemilihan sampel dilakukan dengan metode consecutive sampling. Pemeriksaan sampel dilakukan di laboratorium Prokita pada bulan September 2016 â€“ November 2016. Hasil analisis korelasi Spearman pada hubungan hematokrit dengan SGOT mendapatkan nilai r = 0,162 dan p = 0,419 sednagkan hubungan hematokrit dengan SGPT mendapatkan nilai r = 0,118 dan p = 0,558. Simpulan: Tidak terdapat hubungan hematokrit dengan SGOT dan SGPT pada obesitas sentral. Kata kunci: obesitas sentral, hematokrit, SGOT, SGPT